Clinical Study of Biostimulation with Low-Power Diode Laser After Dental Extractions - Yolanda Collado Murcia; Pia Lopez-Jornet; Francisco Parra Perez (Clinics and Practice)
Introduction: The objective of the present work is to assess the efficacy of photobiomodulation (PBM) with respect to pain, inflammation, and healing after tooth extractions as compared with a sham treatment. Method: A single-blinded, randomized clinical study conducted in a private dental clinic in Murcia, it included 124 patients who needed a tooth extraction, excluding those with medical conditions that could affect healing (such as non-controlled diabetes, immunosuppression, or hemorrhagic disorders). Group I (Experimental): extraction and PBM session with a diode laser (power: 0.5 W, energy 15 J/cm2 for 10–30 s at 1 mm from the tissue). Group II (Sham treatment): tooth extraction and application of inactive PBM. Results: Pain and inflammation decreased similarly in both groups over time. Anxiety decreased in both groups without significant differences (p = 0.776; p = 0.246). There was no evidence that the treatment or location of the extraction had an influence on healing. Suturing the socket increased the likelihood of good healing (p = 0.048), while long procedures reduced it (p = 0.040). Conclusions: PBM is a non-invasive and safe therapy. This study did not show significant differences with respect to the sham treatment. More research is needed with a standardized methodology to better assess its efficacy.